Competency-Based Human Resource Planning in Educational Institutions: A Review of the Literature on Synchronization of Organizational Needs and Educator Competencies - Puspitasari, Ria; Rodiyah, Sinta; Arrauf, Ziddan; Junaidah, Junaidah; Septuri, Septuri (El-Idare: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to analyze competency-based human resource (HR) planning in educational institutions through a literature review, with a focus on the synchronization between organizational needs and educators' competencies. The method used is a systematic literature review of reputable national and international journal articles published within the last five years that are relevant to the research topic. The findings indicate that competency-based HR planning is a strategic process that emphasizes the alignment between organizational needs and the quality of educators' competencies, which include pedagogical, professional, social, and personal aspects, as well as the ability to adapt to technological developments. The needs of educational organizations for educators' competencies are dynamic, particularly in responding to the demands of digitalization and the improvement of educational quality. The synchronization between organizational needs and educators' competencies is a key factor that must be implemented in an integrated manner through policies, HR management systems, and continuous professional development. However, its implementation still faces various challenges, such as limited resources, competency gaps, and the suboptimal implementation of competency-based HR management systems. Therefore, systematic strategies are required, including strengthening continuous training, leveraging technology, and adopting adaptive and data-driven leadership. In conclusion, integrated and sustainable competency-based HR planning can enhance organizational effectiveness and improve the quality of education.